Addressing the contributions of electricity from biomass in Brazil in the context of the Sustainable Development Goals using life cycle assessment methods. (15th February 2022) - Souza, Nariê Rinke Dias de; Souza, Alexandre; Ferreira Chagas, Mateus; Hernandes, Thayse Aparecida Dourado; Cavalett, Otávio
Abstract: The implications of bioenergy deployment for sustainable development goals (SDGs) have been gaining importance worldwide, as bioenergy may contribute to other sustainability impacts besides climate change. Decarbonization of the energy sector can promote major co‐benefits between Climate Action and other SDGs and lead to important tradeoffs. Life cycle assessment (LCA) methods have been proposed to monitor the SDGs as many of them are closely interconnected but often separately studied. A harmonized application of environmental and social LCA can reveal additional relevant aspects of SDGs. This work proposes an interpretation of combined environmental and socioeconomic LCA impacts by comparing the SDG impacts of electricity from sugarcane biomass with other technological options, which altogether represent 96% of the Brazilian electricity matrix. Our analysis indicates that sugarcane electricity has a higher SDGs score (58 points) compared to coal and oil electricity (42 and 47 points, respectively); however, it is lower than natural gas (78). Sugarcane SDG internal normalization related to the biosphere is very close to natural gas, varying only 3–4 points. On the Economy and Society SDG score, sugarcane electricity is also lower than natural gas. Key areas in sugarcane electricity production that need to be enhanced to better contribute to achieving the SDGs include improving its awareness levels, increasing wages and women representation on the workforce, and promoting measures to decrease work accidents as well as the use of fertilizers and pesticides. This approach may help design specific measures for different value chains for them to significantly contribute to the achievement of SDGs.